Analysis of Linktree Based on Argumentation Text Teaching Materials - Mutiara Sany Hasibuan; Khairil Ansari; Safinatul Hasanah Harahap (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this research is to develop Linktree based on argumentation text teaching materials at SMK Negeri 7 Medan. This development research produces products in the form of Linktree argumentation text teaching materials to improve the ability of Medan Vocational High School students to compose coherent arguments, select relevant evidence, and compose persuasive arguments using argumentation text. The research on the development of this teaching material uses the 4D development model. Linktree based argumentation text teaching materials are feasible and bring good development and are effectively used by 11th grade students of SMK Negeri 7 Medan.ds.